2021
DOI: 10.1007/s13595-021-01052-5
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction of drought and frost in tree ecophysiology: rethinking the timing of risks

Abstract: In temperate, boreal and alpine areas, the edges of plant distribution are strongly affected by abiotic constraints. For example, heat waves and drought are major constraints at low latitude and elevation while cold and frost are key factors at high latitude and elevation. Over the next few decades, climate variability is expected to increase, enhancing the probability of extreme events and thus the potential stress imposed by abiotic constraints. Moreover, the likelihood of co-occurring and successive constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 180 publications
(164 reference statements)
0
37
0
1
Order By: Relevance
“…Secondly, our study did not take into account the effect of vegetation age, especially the tree age because data on vegetation age at the global scale are still missing. Previous studies have showed that hydraulic deterioration due to increasing tree age makes trees more susceptible to short‐term drought (Anderegg et al, 2013; Charrier et al, 2021), which can lead to mortality. Thirdly, the impact of wildfires on GPP due to drought were not considered owing to lack of long time series of the wildfire data set.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, our study did not take into account the effect of vegetation age, especially the tree age because data on vegetation age at the global scale are still missing. Previous studies have showed that hydraulic deterioration due to increasing tree age makes trees more susceptible to short‐term drought (Anderegg et al, 2013; Charrier et al, 2021), which can lead to mortality. Thirdly, the impact of wildfires on GPP due to drought were not considered owing to lack of long time series of the wildfire data set.…”
Section: Discussionmentioning
confidence: 99%
“…Water stress resulted in a significant increase in freezing tolerance determined, very probably, by decrease of tissue water content, osmotic adjustment and production of protective solutes [ 172 ]. Two studies [ 70 , 173 ] reported that water deficit significantly enhanced the olive freezing tolerance. Mild water stress and moderate water stress, before the onset of low temperatures (March- September) reduced the freezing injuries and increased freezing tolerance in Arbequina and in Barnea cvs [ 173 ], and in Arbequina, Changlot Real, Frantoio, Hojiblanca and Manzanilla cvs [ 70 ].…”
Section: Agronomic Management For Frost Protectionmentioning
confidence: 99%
“…Two studies [ 70 , 173 ] reported that water deficit significantly enhanced the olive freezing tolerance. Mild water stress and moderate water stress, before the onset of low temperatures (March- September) reduced the freezing injuries and increased freezing tolerance in Arbequina and in Barnea cvs [ 173 ], and in Arbequina, Changlot Real, Frantoio, Hojiblanca and Manzanilla cvs [ 70 ]. Water deficit induced the accumulation of osmotically active solutes and the decrease of RWC.…”
Section: Agronomic Management For Frost Protectionmentioning
confidence: 99%
“…In temperate forests, variation in the season and duration of drought differently affects hydraulic and C dynamics in trees (Gebauer et al, 2020 ; Charrier et al, 2021 ). In summer (growing seasons), trees require more water for transpiration and photosynthesis due to relatively high temperatures and active physiological activities (Morales et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It leads trees to face a high risk of hydraulic failure (Nardini et al, 2013 ), accompanied by C depletion under drought conditions during the growing season (McDowell et al, 2008 ). In winter (dormant seasons), the C reserve is critical for tree survival rather than water transportation because C reserve plays a key role in cold and frost resistance (Charrier et al, 2021 ), while severe embolism (with percentage loss of conductance (PLC) closed to 100%) is not lethal due to the low transpiration and cessation of water absorption (Christensen-Dalsgaard and Tyree, 2014 ; Maruta et al, 2020 ; Mayr et al, 2020 ). These findings suggest that mechanisms of drought-induced tree mortality interact with seasonality in temperate forest ecosystems.…”
Section: Introductionmentioning
confidence: 99%